A phylogenomic and morphometric reassessment of Ovulidae highlights host-related shell shape evolution - E. Nocella; G. Fassio; T. Lemarcis; P. Zaharias; D. Tamagnini; N. de Leo; N. Puillandre; M.V. Modica; M. Oliverio (Molecular Phylogenetics and Evolution, 2026)

Integrative taxonomy of the Clavus canalicularis species complex (Drilliidae, Conoidea, Gastropoda) with description of four new species - A. E. Fedosov; N. Puillandre (Molluscan Research, 2020)

An improved taxonomic sampling is a necessary but not sufficient condition for resolving inter-families relationships in Caridean decapods - L. Aznar-Cormano; J. Brisset; T.-Y. Chan; L. Corbari; N. Puillandre; J. Utge; M. Zbinden; D. Zuccon; S. Samadi (Genetica, 2015)

Molecular Phylogeny, Classification and Evolution of Conopeptides - N. Puillandre; D. Koua; P. Favreau; B. M. Olivera; R. Stöcklin (Journal of Molecular Evolution, 2012)

Large‐scale species delimitation method for hyperdiverse groups - N. PUILLANDRE; M. V. MODICA; Y. ZHANG; L. SIROVICH; M.‐C. BOISSELIER; C. CRUAUD; M. HOLFORD; S. SAMADI (Molecular Ecology, 2012)
Accelerating the description of biodiversity is a major challenge as extinction rates increase. Integrative taxonomy combining molecular, morphological, ecological and geographical data is seen as the best route to reliably identify species. Classic molluscan taxonomic methodology proposes primary species hypotheses (PSHs) based on shell morphology. However, in hyperdiverse groups, such as the molluscan family Turridae, where most of the species remain unknown and for which homoplasy and plasticity of morphological characters is common, shell‐based PSHs can be arduous. A four‐pronged approach was employed to generate robust species hypotheses of a 1000 specimen South‐West Pacific Turridae data set in which: (i) analysis of COI DNA Barcode gene is coupled with (ii) species delimitation tools GMYC (General Mixed Yule Coalescence Method) and ABGD (Automatic Barcode Gap Discovery) to propose PSHs that are then (iii) visualized using Klee diagrams and (iv) evaluated with additional evidence, such as nuclear gene rRNA 28S, morphological characters, geographical and bathymetrical distribution to determine conclusive secondary species hypotheses (SSHs). The integrative taxonomy approach applied identified 87 Turridae species, more than doubling the amount previously known in the Gemmula genus. In contrast to a predominantly shell‐based morphological approach, which over the last 30 years proposed only 13 new species names for the Turridae genus Gemmula , the integrative approach described here identified 27 novel species hypotheses not linked to available species names in the literature. The formalized strategy applied here outlines an effective and reproducible protocol for large‐scale species delimitation of hyperdiverse groups.

ABGD, Automatic Barcode Gap Discovery for primary species delimitation - N. PUILLANDRE; A. LAMBERT; S. BROUILLET; G. ACHAZ (Molecular Ecology, 2012)
Within uncharacterized groups, DNA barcodes, short DNA sequences that are present in a wide range of species, can be used to assign organisms into species. We propose an automatic procedure that sorts the sequences into hypothetical species based on the barcode gap, which can be observed whenever the divergence among organisms belonging to the same species is smaller than divergence among organisms from different species. We use a range of prior intraspecific divergence to infer from the data a model‐based one‐sided confidence limit for intraspecific divergence. The method, called Automatic Barcode Gap Discovery (ABGD), then detects the barcode gap as the first significant gap beyond this limit and uses it to partition the data. Inference of the limit and gap detection are then recursively applied to previously obtained groups to get finer partitions until there is no further partitioning. Using six published data sets of metazoans, we show that ABGD is computationally efficient and performs well for standard prior maximum intraspecific divergences (a few per cent of divergence for the five data sets), except for one data set where less than three sequences per species were sampled. We further explore the theoretical limitations of ABGD through simulation of explicit speciation and population genetics scenarios. Our results emphasize in particular the sensitivity of the method to the presence of recent speciation events, via (unrealistically) high rates of speciation or large numbers of species. In conclusion, ABGD is fast, simple method to split a sequence alignment data set into candidate species that should be complemented with other evidence in an integrative taxonomic approach.

Foot mucus stored on FTA® cards is a reliable and non-invasive source of DNA for genetics studies in molluscs - C. Régnier; O. Gargominy; G. Falkner; N. Puillandre (Conservation Genetics Resources, 2011)

Genetic bottleneck in invasive species: the potato tuber moth adds to the list - N. Puillandre; S. Dupas; O. Dangles; J.-L. Zeddam; C. Capdevielle-Dulac; K. Barbin; M. Torres-Leguizamon; J.-F. Silvain (Biological Invasions, 2008)